The Impact of the Family Relationship on Children’s Spirituality in Tangerang, Indonesia - Juniriang Zendrato (Universitas Pahlawan Tuanku Tambusai, 2021)
This study was conducted to see the impact of the family relationship on the children’s spirituality in Tangerang, Indonesia. Family relationships in this pandemic Covid-19 situation where every family spent more time at home became very important for the children’s spiritual growth. The purposes of this study were to see the children’s background characteristics, family relationships, and religious backgrounds. Descriptive research using a Cross-Sectional Survey Design was applied. A questionnaire with 13 questions was given to 114 children of three Sunday Schools in Tangerang, Indonesia. The results about the background characteristics were 53% of the children were female and between 8-11 years old (70%) as well as living with both parents (93%). Based on the family relationship, 96% of the children had complete parents, had close relationships with mothers (89%), loved both parents (100%), and loved home (96%). Based on the religious background, 94% of mothers attended church regularly and read Bible with the children (77%). Further, 93% of the children had a positive perception of life after death. The conclusion was the family relationship had an impact on the children’s spirituality. Children’s spiritual life grew well if parents lived with them, provided safe and secure homes, and read Bible with them regularly